Tourism Images of Highland Destinations in Pahang, Malaysia - Zainol, Nurul Amirah (2009)
The highland is one of the tourism destinations for people to travel to, other than the beach, wilderness, historical site, lake, city and others. Each of these destinations has their own images that differentiate them from other destinations. The value of understanding the images people have of a destination is important since it affects the individual’s subjective perception and subsequent behaviour and destination choice. In order to investigate the image of highland destinations, a self-administered survey was used to collect data from 1200 respondents both from local and international tourists visiting Cameron Highlands, Fraser’s Hill and Genting Highlands during November and December 2007 Based on the findings, six factors of the tourism image for these highlands as perceived by the tourists were identified namely; 1) “service and infrastructure”, 2) “local attractions and facilities”, 3) “general mood and vacation atmosphere”, 4) “leisure and recreational activities”, 5) “natural surroundings”, and 6) “nature and family-oriented”. All those factors were significantly different among the three highlands except for one factor, namely “services and infrastructures”. Genting Highlands strong points are “services and infrastructures” and “leisure and recreational activities” factors. Meanwhile, Fraser’s Hill came out strongly in terms of “general mood and vacation atmosphere”, “natural surroundings”, and “nature and family-oriented”. Cameron Highlands, on the other hand, had a strong point of “local attractions and facilities” factor. Moreover, the results of the study found significant relationship between tourists’ destination choice and the five image factors which were; 1) “local attractions and facilities”, 2) “general mood and vacation atmosphere”, 3) “leisure and recreational activities”, 4) “natural surroundings” and 5) “nature and family-oriented”. The findings of the study provided theoretical and practical implications for the tourism authorities of Malaysia specifically in the highland area in order to guide them in formulating more precise future marketing strategies.